Vitamin D deficiency as a risk factor for COVID-19 infection in children - E., Adarsh; Jayanna, Malavika; Reddy, Neethu N. (International Journal of Contemporary Pediatrics, 2021)
Background: Vitamin D deficiency is a major public health problem in all age groups. Through its immunomodulatory, anti-inflammatory and antioxidant effects it is shown to have a protective effect in COVID affected children. The objective of the study was to evaluate vitamin D deficiency as a risk factor for developing COVID-19 infection in children and to study the relationship between vitamin D deficiency and the clinical findings in COVID-19 positive children. Methods: A retrospective study of all COVID positive children aged 1 month to 15 years admitted to COVID Paediatric ward of Rajarajeshwari Medical hospital from July 2020-November 2020. All COVID positive children confirmed with RTPCR of age group 1 month to 15 years will be included in the study the age at admission, clinical and laboratory data, and 25‐hydroxycholecalciferol (25‐OHD) levels will be recorded. Patients diagnosed with COVID 19 are divided into 2 groups those with deficient and insufficient vitamin D levels were determined as group 1 and patients with normal vitamin D levels as Group 2. Those with vitamin D Levels below 20ng/ml were determined as group 1 and those with >20 ng/ml as group 2. The various clinical outcomes and laboratory parameters were compared between the two groups. Results: Patients with COVID 19 had significantly lower vitamin D levels 22.39±6.27 (p≤0.0001). Patients in group A that is vitamin D deficient and insufficient group had higher levels of ferritin (p≤0.0001). No significant difference was found between other clinical and laboratory parameters between group 1 and group 2. Conclusions: This is one of the first to evaluate vitamin D levels and its relationship with clinical findings in paediatric patients with covid-19. Although vitamin D does not play a role in the pathogenesis of COVID-19 we do believe its putative role in preventing and treating the disease The results suggest that vitamin D levels may be associated with the occurrence and management of the COVID-19 disease by modulating the immunological mechanism to the virus in paediatric population.